THE EFFECTIVENESS OF GIVING QUIZ AT THE BEGINNING OF LEARNING IN THE DISCOVERY LEARNING MODEL TOWARD LEARNING OUTCOMES STUDENTS ON BUFFER SOLUTION MATERIA IN CLASS XI IPA OF SMA NEGERI 3 PANGKEP - Hekin, Yasinta Bungkang; Sulatry, Taty; Allo, Eda Lolo (Universitas Negeri Surabaya, 2023)
A quiz at the beginning of learning is very important to assess students’ learning readiness. Readiness to learn is a condition that must be owned by students because it will make it easier for students to accept and understand the material presented. Good learning readiness will also encourage students to be active in the learning process to improve student learning outcomes. This study aims to determine the level of effectiveness of giving quizzes at the beginning of quiz-assisted learning in the discovery learning model on student learning outcomes in the buffer solution material. This research was conducted at SMA Negeri 3 Pangkep in class XI IPA 2 with a total of 30 students. Data collection is done by presenting a quiz at the beginning of each lesson, a final test as an evaluation, observing student activities, and observing the implementation of learning. Data analysis used descriptive statistical analysis. Learning is said to be effective if students’ learning outcomes are at an N-gain of 0.3 to 1.00. Based on the results of data analysis, it was concluded that giving quiz at the beginning of learning in the discovery learning model toward learning outcomes students on buffer solution materia in class XI IPA of SMA Negeri 3 Pangkep was effective. With an N-gain value of 0.45 in the medium category.